Strengthening Public Understanding of Household K3 as an Effort to Prevent Accidents and Daily Health Risks in Ujung Padang Subdistrict - Nayodi Permayasa; Asdi Lastari; Fauziah Gusvita Syarah; Rahmat Rizki Siregar (International Journal of Community Service Implementation, 2025)
Occupational Safety and Health (K3) is not only important in formal work environments, but is also very relevant in home life. Many domestic accidents occur due to a lack of public understanding of the basic principles of K3, such as electrical hazards, fires, and handling minor injuries. This community service activity aims to improve public understanding in Ujung Padang Village, Padangsidimpuan City, regarding the importance of implementing K3 households as an effort to prevent daily risks. The implementation method is carried out directly through lectures, interactive discussions, demonstrations, and simulations. A total of 40 residents actively participated in this activity. Evaluation using pre-tests and post-tests showed a significant increase in participants' understanding of hazard identification and preventive measures at home. The results of the activity prove that community-based K3 education is effective in forming an alert attitude and safe behavior. This program is expected to be a model for sustainable development to create a culture of safety awareness from home